Evaluasi Kebijakan Perencanaan Obat Instalasi Farmasi Dinas Kesehatan Kota Semarang - Fauzia Halida; Sudiro Sudiro; Johanes sugiarto (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2017)
Based on the Management of Public Drug and Health Supply Profile, the availability rate of drugs in Pharmaceutical Unit Health Department Semarang 2013-2015 was 107%, 110%, and 109% .The availability rate of drugs in Pharmaceutical Unit Health Department Semarang for 3 years in a row exceeds 100% showed a weakness in drugs planning process. Objective of this study was to analyse the planning process of drugs. This was descriptive research with qualitative method. Research subject is the primary respondents who developed drug planning policy and triangulation respondents who implement the drugs planning policy. Research object was Pharmaceutical Unit Health Department Semarang and Puskesmas. Data collected by observation, documentation study and depth interview and analysed using content analysis. The result showed that drugs selection was according to FORNAS and DOEN stated by Ministry of Health. The compilation stage of drugs application using data according to LPLPO and LB-1. The calculation of drugs necessity used combination method between consumption method used by clinic and epidemiology method for program medicine. Based on the consumption method formula, the current leadtime in Pharmaceutical Unit Health Department Semarang was too high (6 months) which caused the supplies more than 100 %. The drugs necessity projection budget already sufficient because it was supported from several sources, such as APBD2, APBD1, APBN, DAK, JKN. The adjustment of drugs supply planning used VEN Analysis. It is suggested that Pharmaceutical Unit Health Department Semarang should shortened the current leadtime and increase the socialization of drugs guidelines therefore Puskesmas able to implement the epidemiology method